A Fatal Case of Cervical Hemorrhage After Fine Needle Aspiration and Core Needle Biopsy of the Thyroid Gland. (September 2015) - Kakiuchi, Yasuhiro; Idota, Nozomi; Nakamura, Mami; Ikegaya, Hiroshi
<x xml:space="preserve">Abstract</x> Abstract Fine needle aspiration (FNA) and core needle biopsy (CNB) are recognized to be safe, useful, and inexpensive diagnostic tools for the evaluation of thyroid nodules. However, complications can arise during the procedure, albeit rarely and typically minor in nature. We report here an unusual fatal case of massive hematoma of the neck after FNA and CNB that may have caused airway obstruction. A 68-year-old Japanese woman underwent both procedures and was found dead at home later the same day. Although severe complications of FNA or CNB such as major bleeds or deaths are rarely reported, clinicians and forensic pathologists should be cognizant that complications can arise.